A Rare Case of Dilated Cardiomyopathy in Sjögren’s Syndrome - Pradnya Diggikar; Tushar Pancholi; Sreevidya Yekkaluru; Hansini Raju Reddy; Akhilesh Jagirdar (Journal of Clinical and Diagnostic Research)
Dilated Cardiomyopathy (DCM) is a rare but significant complication in patients with primary Sjögren’s Syndrome (pSS), a systemic autoimmune disease that primarily affects the exocrine glands. Cardiac involvement in pSS is uncommon, making the recognition of DCM in these patients crucial for timely intervention. This is a case of a 44-year-old female with well-controlled hypertension who developed progressively worsening shortness of breath, chest pain and bilateral pedal oedema. She also had a two-month history of dry eyes and dry mouth, indicative of sicca symptoms. Clinical examination revealed signs of fluid overload, a pansystolic murmur and sicca features. Electrocardiogram (ECG) and echocardiography demonstrated severe left ventricular dysfunction with an ejection fraction of 15%, consistent with DCM. Laboratory investigations revealed elevated N-terminal pro b-type natriuretic peptide (NT-proBNP) levels and positive anti-Ro52 and anti-La antibodies, pointing to an autoimmune aetiology. Cardiac Magnetic Resonance (CMR) Imaging confirmed non ischaemic DCM, ruling out ischaemic causes. The patient was diagnosed with DCM secondary to pSS. She was treated with diuretics, Angiotensin Converting Enzyme (ACE) inhibitors and immunosuppressive therapy, including methylprednisolone and a tapering course of prednisolone over six months. Significant clinical improvement was observed on follow-up. This case highlights the importance of recognising autoimmune aetiologies, such as pSS, in patients presenting with unexplained cardiomyopathy. Early diagnosis and interdisciplinary management are essential in preventing severe cardiac complications and improving patient outcomes in rare presentations of Sjögren-associated cardiomyopathy